Utilization of Gravity Satellite Data to Imaging Subsurface Conditions, Case Study: Lake Toba, North Sumatera. Issue 1 (October 2021) - Abdurrahman, Dadi; Setianingsih,; Alawiyah, Susanti; Kadir, Wawan Gunawan A.; Santoso, Djoko; Dahrin, Darharta; Gunawan, Indra
Abstract: The purpose of this study is to utilize satellite gravity data for free to interpret subsurface conditions. The data can be obtained from the topex site with a latitude range is +/-80, 738. The author tries to interpret the gravity data for Lake Toba, North Sumatra. The area is attractive because it has a sizeable geological object in the form of a large lake and a fault called the Sumatran fault. This gravity data is processed like ordinary gravity processing so that Complete Bouguer Anomaly (CBA) is obtained, then regional-residual separation is carried out using a moving average. From CBA, it can be seen that there are two closures just below Lake Toba. There are two possible chambers under Lake Toba, namely the central and southern parts. In addition, it is also clear that the lineament of the Sumatran fault is also visible, as well as three other lineaments which may be faults that are not identified from the surface. So, we can take advantage of this free gravity satellite data for interpretation of sizeable geological objects that can be applied to other areas. It is helpful to know the general picture of regional geology before conducting a more detailed survey.